IT TAKES MORE THAN CLAY TO BUILD A MAN: THE IDENTITY OF THE MALE CHARACTER IN THE SHORT STORY “THE MESSAGE”, BY CLARICE LISPECTOR (Muitas Vozes, 2021)
In order to write, women had to struggle to conquer the right to write and to represent themselves from their own point of view. By conquering this right, the woman writer began to also portray men as characters of their novels, chronicles, short stories and poems; among those who ventured into this challenge, we highlight Clarice Lispector. Counting with a large bibliography about her work, especially on the female character, we propose a study focused on a little discussed side of Lispector’s literature: the male character. In this context, we highlight, as the main objective to analyze the male character of the tale “A mensagem”, from A legião estrangeira (1999), to understand how his identity is built through the conducts required to man in his youth. In the light of scholars of masculinity, such as Nolasco (2001), Oliveira (2004), Bourdieu (2016), among others, and of identity (BAUMAN, 2005; HALL, 2015), our reading points to a masculine representation inscribed in an ambiguous reality, which sometimes emphasizes hegemonic traces of its masculinity, and in others, it is turned away, bringing to light the human frailty, which is independent of gender.